Public Participation in Policy Making: Evidence from a Citizen Advisory Panel. Issue 6 (2nd November 2022) - Chan, Yolande E.; Krishnamurthy, Rashmi; Mann, Janelle; Sabherwal, Rajiv
Abstract: Research on mechanisms that lead to the successful involvement of citizens, particularly citizen advisory panels, in policy-making processes is limited. In this paper, we use unique longitudinal data to examine how power and information asymmetries within a citizen advisory group influence a policy-making process and its outcomes. We studied the case of a public hospital where the hospital management involved a citizen advisory panel (CAP) and the general public to help decide what hospital services should be cut. We found that female CAP members perceived more power asymmetry while male CAP members experienced more process satisfaction. Older CAP members perceived more information asymmetry. Our findings show that the policy-making management team's commitment to the process can reduce skepticism by citizens regarding the value of their involvement and facilitate decision quality and process satisfaction. Policy makers were able to effectively share technical policy information with citizens in an easily digestible format over time and to achieve effective citizen participation in the policy-making process.